A seed morphometry study of selected species of Bulbophyllum and Dendrobium (Orchidaceae) in relation to their dispersals - POPI APRILIANTI; ELIZABETH HANDINI; DWI MURTI PUSPITANINGTYAS (Society for Indonesian Biodiversity, 2021)
Abstract. Aprilianti P, Handini E, Puspitaningtyas DM. 2021. A seed morphometry study of selected species of Bulbophyllum and Dendrobium (Orchidaceae) in relation to their dispersals. Biodiversitas 22: 5564-5571. Bulbophyllum and Dendrobium are the two largest genera of Orchidaceae. The seed morphometry studies of Bulbophyllum and Dendrobium, mainly from Southeast Asia are still poorly reported. The research aimed to characterize seeds micromorphometry of selected species of Bulbophyllum and Dendrobium, namely Bulbophyllum graveolens, B. macranthum, B. phalaenopsis, Dendrobium bicaudatum, and D. bifalce in relation to their dispersal mechanisms. Twenty seeds of each species were studied using light and scanning electron microscope (SEM). Qualitative characters, such as seed shape, testa cell shape, wall structure, and its orientation and quantitative data, such as seed and embryo were analyzed. The results showed that the shape of the seeds of all the species was fusiform. The testa cell walls were smooth and covered by waxes. The anticlinal walls were raised and thickened. Bulbophyllum and Dendrobium can be differentiated in the orientation of testa cells, which is spirally oriented in Bulbophyllum and parallel to the long axis in the Dendrobium. There are no large variations in seed and embryo volume as well as seed air space (SAS) in different taxa. The SAS value can be used to predict the dispersal mechanism and distribution area of the orchid species. Unfortunately, the SAS values are not always positively correlated with the distribution area and other factors inhibit the spread of the species.